Beberapa Catatan tentang Buku Teks Pelajaran di Sekolah - Anwar Efendi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Text book is books that function as student reference as learning media (instructional). Text books have important role on every education system, inside class or outside class. Text book content developed based on prevailing curriculum. Therefore, text book must standardized, and seen as collection of knowledge about every side of life. Its have to be prepared on its comprehensiveness and its presentation, so can give facility to autonomous learning activity, on its substance or its method. Text book is a part of learning equipment that very important to accelerate, enhance, and educate student. Test books must be designed carefully to function as effective learning tools.Â